PEMBAHARUAN HUKUM KELUARGA ISLAM DALAM MENGHADAPI TANTANGAN SOSIAL KONTEMPORER PERSEPEKTIF MAQASHID SYARIAH - La Harisi, Isnain; M. Wahid Abdullah (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study examines the necessity of reforming Islamic family law in response to contemporary social challenges from the perspective of Maqashid Syariah. The rapid changes in social norms, particularly regarding gender roles, divorce, and women's rights, call for a flexible approach to Islamic law that remains rooted in the principles of justice and welfare. Maqashid Syariah, or the higher objectives of Islamic law, provide a theoretical framework that focuses on preserving religion, life, intellect, lineage, and wealth. Through qualitative research, particularly literature review and content analysis, this study identifies key areas where Islamic family law can be reformed to better address contemporary issues without compromising core Islamic values. The findings reveal that gender roles within the family should be more equitable, with greater recognition of women's roles both inside and outside the household. In the area of divorce, the law must ensure justice and protection for women and children, aligning with the objectives of Maqashid Syariah to safeguard life and lineage. Additionally, women’s rights in inheritance and financial matters should be strengthened. This study demonstrates that the principles of Maqashid Syariah offer a robust and adaptable framework for reforming Islamic family law to meet the needs of contemporary society while maintaining the integrity of Islamic teachings. Keywords: contemporary challenges, Islamic family law, legal reform,Maqashid Syariah.